President and the legislative process: the use of the veto right in Lithuania - Talat-Kelpša, Laimonas (Politologija, 1998)
After the Soviet collapse, Lithuania introduced a constitutional model the political scientists usually name as 'semi-presidential regime.' Three principal features characterize semi-presidential government: (1) president-nominated prime minister, (2) presidential power to dissolve parliament, and (3) cabinet reliance on parliamentary support. Beyond doubt, there are other important qualities, such as considerable de jure and de facto presidential powers. Yet the current experience of semi-presidential regimes demonstrates the imbalance that arises (develops) between the de jure and de facto presidential authorities, and one has to acknowledge that as a matter of fact these powers almost never go in accord.Application of constitutional provisions often depends on the present political environment and particular political personalities. These are the factors most difficult to foresee. But the general trends of development still can be predicted. One may post a hypothesis that the semi-presidential system of Lithuania actually is not so much semi-presidential as it can be read from the Constitution.This article considers the presidential role in legislation. If we establish the president as a part of the executive, we may expect his active involvement in legislation aiming to direct appropriately governmental policies. Still, even an unqualified look reveals that the presidential involvement in the legislative process in Lithuania is limited. What explanations one might expect?The article consists of four chapters. In the first one, the choice of the veto use as an analytical object is motivated. In the second, intensity of the veto used is considered, while in the last two empirical data collected for this particular article is processed. In the conclusions, the place of the president in the political system of Lithuania is redefined. It may seem possible to suggest that Lithuania is increasingly attaining the features of a parliamentary system, save becoming the one.
Keywords: -